2013
DOI: 10.1603/an12137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidative Enzyme Activity, Glycogen, Lipid, Protein, and Malondialdehyde Content in Cadmium-Treated Galleria mellonella Larvae

Abstract: In this study, we analyzed the effects of cadmium (1.25, 2.5, 5, 10, 20, and 40 mg per 100 g of nutrient) on total protein, lipid, and glycogen levels, lipid peroxidation (MDA), superoxide dismutase (SOD) and catalase (CAT) activities, and metal accumulation in Galleria mellonella L. High concentrations of Cd (20 and 40 mg) significantly lowered total protein, lipid, and glycogen levels. MDA level significantly increased when the nutrient contained 5 mg and more of Cd, whereas SOD activity significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 46 publications
5
18
0
Order By: Relevance
“…The increasing activity of CAT is related with an adaptive response to remove hydrogen peroxide (Dorval et al., ). It has also been reported that insects have higher level of CAT activity than mammals (Ahmad and Pardini, ) and CAT activity may be inhibited when low level of hydrogen peroxide is present (Krishnan and Kodrik, ; Emre et al., ). Similar results were found in some lepidopteran insects upon exposure of various pesticides or allelochemicals (Krishnan and Kodrik, ; Aslantürk et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increasing activity of CAT is related with an adaptive response to remove hydrogen peroxide (Dorval et al., ). It has also been reported that insects have higher level of CAT activity than mammals (Ahmad and Pardini, ) and CAT activity may be inhibited when low level of hydrogen peroxide is present (Krishnan and Kodrik, ; Emre et al., ). Similar results were found in some lepidopteran insects upon exposure of various pesticides or allelochemicals (Krishnan and Kodrik, ; Aslantürk et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, these toxicological influences may induce the defense mechanisms to compensate for physiological problems during stress conditions. It is well known that antioxidants are among the major components of the immune system in the detoxification of harmful xenobiotics and endobiotics such as herbicides, insecticides, chemical carcinogens, and other organic and inorganic environmental pollutants (Büyükgüzel et al., ; Aslantürk et al., ; Emre et al., ), and they play crucial role in the inactivation of activated oxygen metabolites. Antioxidant system is divided into two groups as enzymatic (superoxide dismutase (SOD), catalase (CAT), glutathione‐ S ‐transferase (GST), and peroxidases) and nonenzymatic (phenol‐containing compounds, vitamin E, vitamin C, and high and low molecular thiol) components in animals including insects (Felton and Summers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zn and Cu connect to the cytosol metallothionein in the midgut of many organisms and, as such, are essential elements but at high concentrations they can be toxic [ 144 ]. Cd is highly toxic, even at a low concentration and can create mutations in the organism [ 145 ]. The effect of heavy metals on an index such as relative growth rate (RGR) is quite various.…”
Section: Influence Of Heavy Metals In the Response Of Plants To Bimentioning
confidence: 99%
“…On the other hand, it is known that elements such as Cd are highly toxic, even at a low concentration and have a broad impact on insects causing mutations [ 145 ]. Besides, there are some examples of [ 178 , 179 ] harmful effects of this metal on insects.…”
Section: Effects Of Heavy Metals On Insects Including Aphidsmentioning
confidence: 99%
“…7 For example, the effects of environmental factors on feeding intake can take on indicators of nutritional influence. 8 The effect of heavy metals on an index such as RGR is quite various.…”
Section: Introductionmentioning
confidence: 99%